PENGARUH DESENTRALISASI FISKAL DAN KETERGANTUNGAN KEUANGAN DAERAH TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA PROVINSI SULAWESI SELATAN - Maulana, Syahrial (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2023)
The Human Development Index is a composite index that measures human development from three basic perspectives: longevity and healthy living, knowledge and a decent standard of living. The purpose of this study was to examine the effect of fiscal decentralization and regional economic dependence on the human development index in districts/cities in South Sulawesi Province. This research is quantitative in nature. The data used in this study used time series data from 2021-2022 (2 years) and cross section data of 24 districts / cities, so the total sample was 48 data which included data on fiscal decentralization, regional financial dependence and human development index in South Sulawesi Province which were processed and analyzed by multiple linear regression. The results of this study successfully confirmed that fiscal decentralization has a positive and significant effect on the Human Development Index; while regional financial dependence has no significant effect on the Human Development Index.